Titanium alloy with medium-high strength, high toughness and damage tolerance as well as preparation method and application of titanium alloy
By adjusting the content of Al, Cr, V and other elements in titanium alloys and adopting specific preparation processes, the gap between the medium, high strength, high toughness, and high toughness damage tolerance in existing titanium alloys is solved, and high strength, high toughness and low cost titanium alloy materials are realized, suitable for structural parts applications in aerospace and other fields.
Patent Information
- Application Number
- CN202411811498.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-10
AI Technical Summary
There is a gap in the gap between medium, high strength, high toughness, and high toughness damage tolerance titanium alloys in the existing titanium alloy system, which cannot meet the multi-dimensional material layout requirements for structural parts of different strengths in aerospace and other fields.
It is provided with a medium-high strength and high toughness damage tolerance, and its components include Al: 5.0% to 7.0%, Cr: 2.5% to 4%, V: 2.5% to 5.0%, O: 0.05% to 0.15%. Through specific electrode preparation and ingot smelting processes, the content of impurity elements is controlled to ensure the high phase change point and toughness of the alloy.
The performance of tensile strength Rm≥1000MPa, yield strength Rp0.2≥880MPa, elongation A≥18%, fracture toughness KIC≥120MPam1/2, fatigue crack propagation rate da/dN≤8.92×10-6mm/cycle was achieved, and the raw material cost was low, and it was suitable for aviation structural parts and other fields.
Smart Images

Figure CN119685653A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of titanium alloy material preparation, and in particular relates to a titanium alloy with medium-high strength, high toughness and damage tolerance, a preparation method and application thereof. Background Art
[0002] With the rapid development of the aviation industry, aviation structural parts have new and diverse demands for lightweight medium and high strength titanium alloys. Now, it is no longer limited to highlighting a single performance advantage, but based on actual service needs and design goals, focusing on multi-dimensional considerations such as low cost, high performance, and high stability, striving to create new titanium alloy products with excellent comprehensive performance.
[0003] Back in the 1970s, the U.S. Air Force took the lead in introducing the concept of "damage tolerance" in aircraft structural design. Based on this, it has successively developed titanium alloys such as Ti-6A1-4V (β-ELI, a titanium alloy containing β phase and ultra-low interstitial element content) with a strength of 900MPa, and Ti-6-22-22S (Ti-6A12Sn-2Zr-2Mo-2Cr-0.2Si) with a strength of 1000MPa, which have excellent comprehensive mechanical properties. In the structural composition of the fourth-generation fighter F-22, the two low-gap damage-tolerant titanium alloys Ti-6Al-4V and Ti-6-22-22S account for up to 41% of the structural weight. It can be seen that damage-tolerant titanium alloys are gradually occupying a dominant position in the application of aircraft structural parts.
[0004] Based on the domestic situation, in order to meet the new international standards and requirements for titanium alloy damage tolerance, my country has actively made plans and carried out special research on high-strength, high-toughness and high-damage-tolerance titanium alloys. After years of research and exploration, we have successfully developed a high-strength, high-toughness damage-tolerant titanium alloy TC21 (nominal composition is Ti-6Al-2Zr-2Sn-3Mo-1Cr-2Nb-0.1Si, tensile strength Rm≥1100MPa, fracture toughness K IC ≥70MPam 1 / 2 ), and the medium-strength and high-toughness damage-tolerant titanium alloy TC4-DT (nominal composition Ti-6Al-4V, tensile strength Rm ≥ 860MPa, fracture toughness K IC ≥90MPam 1 / 2 ), and has been applied on a large scale in scenarios of key load-bearing components of aircraft.
[0005] However, in the existing titanium alloy system, there is still a gap in the medium-high strength and high toughness damage tolerant titanium alloy between the high-strength and high-toughness damage tolerant titanium alloy TC21 and the medium-strength and high-toughness damage tolerant titanium alloy TC4-DT. Therefore, it is urgent to develop a medium-high strength and high toughness damage tolerant titanium alloy to improve the material layout of "high, medium and low" levels of reasonable matching in the application of different strength structural parts in my country's aerospace and other related fields.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The purpose of the present invention is to overcome the disadvantages of the above-mentioned prior art and provide a titanium alloy with medium-high strength, high toughness and damage tolerance, a preparation method and application thereof.
[0008] To achieve the above object, the present invention provides the following technical solutions:
[0009] On the one hand, the present invention provides a titanium alloy with medium-high strength, high toughness and damage tolerance, which includes, by weight percentage, Al: 5.0% to 7.0%, Cr: 2.5% to 4%, V: 2.5% to 5.0%, O: 0.05% to 0.15%, C≤0.02%, N≤0.01%, H≤0.01%, Si≤0.01%, Fe≤0.08%, and the balance is Ti and unavoidable impurity elements, wherein the total amount of impurity elements is less than 0.05%. In order to ensure the damage tolerance related performance, the impurity elements in the product need to be controlled.
[0010] Specifically, the equivalent range of Al and Mo in the titanium alloy satisfies: 15wt.%≤[Al]eq+[Mo]eq≤17.5wt.%, and 0.9≤[Al]eq / [Mo]eq≤1.2, which can ensure a higher phase transition point of the alloy, facilitate alloy processing, prevent the precipitation of brittle ɑ2 phase during heat treatment, and improve the strength and toughness of the alloy.
[0011] On the other hand, the present invention provides a method for preparing the titanium alloy with medium-high strength, high toughness and damage tolerance as described above, the specific steps are as follows:
[0012] Step 1: Electrode preparation:
[0013] Complete weight calculation, weighing, mixing, electrode block pressing and electrode welding of titanium sponge, master alloy and other elemental metals according to weight percentage to form consumable electrodes;
[0014] Among them, sponge titanium should meet C≤0.008%, N≤0.005%, H≤0.003%, Si≤0.01%, Fe≤0.04%, Sn≤0.03%, Cl≤0.03%, and the particle size is less than 5mm; the intermediate alloy is vanadium aluminum alloy, and its impurity elements should meet C≤0.05%, N≤0.03%, H≤0.01%, S≤0.01%, P≤0.01%, B≤0.01%, Si≤0.02%, Fe≤0.10%, and the particle size is less than 1mm; in order to reduce the risk of Cr segregation, it is required that single Cr is added in the form of powder, and the impurity elements meet C≤0 .005%, N≤0.01%, H≤0.005%, Si≤0.01%, Fe≤0.10%, and the powder particle size is less than 100 mesh; the remaining Al element is added in the form of single Al, and the impurity elements meet the requirements of C≤0.01%, N≤0.001%, H≤0.003%, Si≤0.01%, Fe≤0.08%, and the particle size is less than 3mm; the above raw materials are added into a mixer and mixed evenly, and then pressed into electrode blocks, and the weight of a single electrode block is required to be 10-40kg. In order to ensure the uniformity of the ingot composition, each electrode block is pressed separately, and then the electrode blocks are assembled and welded into consumable electrodes;
[0015] The electrode block assembly welding should be completed within 5 hours after the electrode block is pressed and placed in the welding box for vacuuming. The welding should be completed in a plasma welding box under argon protection. The argon pressure inside the welding box is required to be 1×10 6 ~1×10 7 Pa, at the same time, monitor and detect the O and N elements inside the welding box before and during welding to ensure that the O content in the welding box is less than 500ppm and the N content is less than 800ppm;
[0016] Step 2: Ingot smelting:
[0017] First, a vacuum consumable arc furnace is used to melt the consumable electrode once to obtain a primary ingot, then the primary ingot is turned around and melted twice to obtain a secondary ingot, and finally the secondary ingot is turned around and melted three times to obtain a finished ingot. It is required that the time interval from the consumable electrode to the primary melting is less than 8 hours, the time interval between the primary melting and the secondary melting is less than 12 hours, and the time interval between the secondary melting and the tertiary melting is less than 15 hours, so as to ensure the uniformity of the ingot composition;
[0018] The smelting of the primary ingot and the secondary ingot are both carried out by vacuum consumable arc smelting. To ensure smooth exhaust of the electrode during the primary smelting process, the crucible ratio (electrode diameter / crucible diameter) is required to be less than 0.71. The primary ingot is firstly washed with a high-pressure air gun and clean water to remove dust on the surface and then dried. The gray and blackened positions on the surface of the primary ingot are then machined to completely remove the solidified shell at the position with a high content of impurity elements. The surface of the secondary ingot is brushed and polished to remove some volatile impurities in the smelting process.
[0019] The parameters of the above three smeltings are: in the first smelting, the vacuum degree of the smelting furnace is 0.5-0.8Pa, the leakage rate is less than 0.6Pa / min, the smelting current is 10-25kA, and the smelting voltage is 26-38V. After the first smelting is completed, the vacuum cooling time of the first ingot in the crucible is 7-9h, and the vacuum degree is less than 1Pa; in the second smelting, the leakage rate is controlled to be less than 0.5Pa / min, the vacuum degree is less than 0.5Pa, the smelting current is 13-27kA, The smelting voltage is 28-42V. After the secondary smelting, the secondary ingot is vacuumed and cooled in the crucible for 8-10 hours, and the vacuum degree is less than 0.8Pa. During the tertiary smelting, the leakage rate is controlled below 0.3Pa / min, the vacuum degree is 0.01-0.1Pa, the smelting current is 4-25kA, and the smelting voltage is 20-43V. After the tertiary smelting, the finished ingot is vacuumed and cooled in the crucible for 9-12 hours, and the vacuum degree is less than 0.5Pa.
[0020] Step 3: Hot forming of bars:
[0021] First, the finished ingot is heated to 930-1080°C to complete 1-2 rounds of blanking forging, then 2-4 rounds of intermediate forging are completed at 770-910°C, and finally 2-5 rounds of forming forging are completed at 750-800°C to form bars with specifications of Φ150mm-Φ450mm;
[0022] Step 4: Heat treatment:
[0023] The obtained rod is kept at 750-800°C for 2h, and then subjected to AC ordinary annealing heat treatment to obtain a titanium alloy with medium-high strength, high toughness and damage tolerance.
[0024] Specifically, the titanium alloy has a tensile strength Rm ≥ 1000 MPa and a yield strength Rp 0.2 ≥880MPa, elongation A≥18%, section shrinkage Z≥45%, fracture toughness K IC ≥120MPam 1 / 2 , fatigue crack growth rate da / dN (ΔK=11)≤8.92×10 -6 mm / cycle.
[0025] In another aspect, the present invention provides a titanium alloy with medium-high strength, high toughness and damage tolerance as described above, or a titanium alloy prepared by the method for preparing the titanium alloy with medium-high strength, high toughness and damage tolerance as described above, and its use in aviation structural parts.
[0026] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0027] The titanium alloy with medium-high strength and high toughness and damage tolerance provided by the present invention has a tensile strength Rm≥1000MPa and a yield strength Rp 0.2 ≥880MPa, elongation A≥18%, section shrinkage Z≥45%, fracture toughness K IC ≥120MPam 1 / 2 , fatigue crack growth rate da / dN≤8.92×10 -6 mm / cycle, its various mechanical properties have obvious advantages over TC4-DT, its strength is 100MPa lower than TC21, and its other properties are significantly better than TC21 alloy.
[0028] Furthermore, when preparing titanium alloys with medium-high strength, high toughness and damage tolerance, only Al, V and Cr elements are added, and the more expensive V element is added in a smaller amount, while Al and Cr elements are relatively cheap. The raw material cost is lower than that of TC21 and TC4-DT, which further reduces the production cost and helps it to be applied in more fields.
[0029] Furthermore, when preparing titanium alloys with medium-to-high strength and high toughness and damage tolerance, in order to reduce the influence of impurity elements on their damage tolerance-related properties, the requirements for the selection and use of raw materials, the requirements for the vacuum degree of the ingot preparation cooling process and the air contact time are clarified, and the content of impurity elements in the ingot is reduced by flushing and machining the surface of the first ingot and brushing the surface of the second ingot to improve the purity of the ingot composition. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The accompanying drawings are incorporated in and constitute a part of this specification and, together with the description, serve to explain the principles of the present invention.
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0032] Figure 1 This is a macroscopic structural photograph of the head of the titanium alloy Φ340 mm ingot of Example 1 of the present invention;
[0033] Figure 2This is a low-magnification microstructure photograph of the head of a titanium alloy Φ200 mm bar in Example 1 of the present invention;
[0034] Figure 3 The head T of the titanium alloy Φ200 mm bar of Example 1 of the present invention β -25℃ air-burned tissue photos;
[0035] Figure 4 This is a metallographic photograph of the head of a titanium alloy Φ200 mm bar after ordinary annealing in Example 1 of the present invention;
[0036] Figure 5 This is a macroscopic structural photograph of the head of the titanium alloy Φ720 mm ingot of Example 2 of the present invention;
[0037] Figure 6 This is a macroscopic structural photograph of the tail of the titanium alloy Φ720 mm ingot of Example 2 of the present invention;
[0038] Figure 7 This is a graph showing the Al content results at nine points in the transverse direction of the titanium alloy 720 mm ingot of Example 2 of the present invention;
[0039] Figure 8 This is a graph showing the V content results at nine points in the transverse direction of the titanium alloy 720 mm ingot of Example 2 of the present invention;
[0040] Fig. 9 This is a graph showing the Cr content at nine points in the transverse direction at the head and tail of a titanium alloy 720 mm diameter ingot according to Example 2 of the present invention;
[0041] Fig.10 This is a graph showing the O content results at nine points in the transverse direction at the head and tail of a titanium alloy 720 mm diameter ingot according to Example 2 of the present invention;
[0042] Fig.11 This is a low-magnification microstructure photograph of the head of the titanium alloy Φ400 mm bar of Example 2 of the present invention;
[0043] Fig.12 This is a low-magnification microstructure photograph of the tail of the titanium alloy Φ400 mm bar of Example 2 of the present invention;
[0044] Fig.13 This is a metallographic photograph of the head of a titanium alloy Φ400 mm bar in Example 2 of the present invention after ordinary annealing;
[0045] Fig.14 The present invention is a flow chart of a method for preparing a high-strength, high-toughness, damage-tolerant titanium alloy. DETAILED DESCRIPTION
[0046] Here, exemplary embodiments will be described in detail, and examples thereof are shown in the accompanying drawings. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. Instead, they are only examples consistent with some aspects of the present invention as detailed in the appended claims.
[0047] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0048] On the one hand, the present invention provides a titanium alloy with medium-high strength, high toughness and damage tolerance, which includes, by weight percentage, Al: 5.0% to 7.0%, Cr: 2.5% to 4%, V: 2.5% to 5.0%, O: 0.05% to 0.15%, C≤0.02%, N≤0.01%, H≤0.01%, Si≤0.01%, Fe≤0.08%, and the balance is Ti and unavoidable impurity elements, wherein the total amount of impurity elements is less than 0.05%. In order to ensure the damage tolerance related performance, the impurity elements in the product need to be controlled.
[0049] Specifically, the equivalent range of Al and Mo in the titanium alloy satisfies: 15wt.%≤[Al]eq+[Mo]eq≤17.5wt.%, and 0.9≤[Al]eq / [Mo]eq≤1.2, which can ensure a higher phase transformation point of the alloy, facilitate alloy processing, and prevent the precipitation of brittle ɑ2 phase during heat treatment to improve the strength and toughness of the alloy.
[0050] On the other hand, the present invention provides a method for preparing the titanium alloy with medium-high strength, high toughness and damage tolerance as described above, such as Fig.14 As shown, the specific steps are as follows:
[0051] Step 1: Electrode preparation:
[0052] Complete weight calculation, weighing, mixing, electrode block pressing and electrode welding of titanium sponge, master alloy and other elemental metals according to weight percentage to form consumable electrodes;
[0053] Among them, sponge titanium should meet C≤0.008%, N≤0.005%, H≤0.003%, Si≤0.01%, Fe≤0.04%, Sn≤0.03%, Cl≤0.03%, and the particle size is less than 5mm; the intermediate alloy is vanadium aluminum alloy, and its impurity elements should meet C≤0.05%, N≤0.03%, H≤0.01%, S≤0.01%, P≤0.01%, B≤0.01%, Si≤0.02%, Fe≤0.10%, and the particle size is less than 1mm; in order to reduce the risk of Cr segregation, it is required that single Cr is added in the form of powder, and the impurity elements meet C≤ 0.005%, N≤0.01%, H≤0.005%, Si≤0.01%, Fe≤0.10%, and the powder particle size is less than 100 mesh; the remaining Al element is added in the form of single Al, and the impurity elements meet the requirements of C≤0.01%, N≤0.001%, H≤0.003%, Si≤0.01%, Fe≤0.08%, and the particle size is less than 3mm; the above raw materials are added into a mixer and mixed evenly, and then pressed into electrode blocks, the weight of a single electrode block is required to be 10-40kg, and each electrode block is pressed separately to ensure the uniformity of the ingot composition, and then the electrode blocks are assembled and welded into consumable electrodes;
[0054] The electrode block assembly welding should be completed within 5 hours after the electrode block is pressed and placed in the welding box for vacuuming. The welding should be completed in a plasma welding box under argon protection. The argon pressure inside the welding box is required to be 1×10 6 ~1×10 7 Pa, at the same time, monitor and detect the O and N elements inside the welding box before and during welding to ensure that the O content in the welding box is less than 500ppm and the N content is less than 800ppm;
[0055] Step 2: Ingot smelting:
[0056] First, a vacuum consumable arc furnace is used to melt the consumable electrode once to obtain a primary ingot, then the primary ingot is turned around and melted twice to obtain a secondary ingot, and finally the secondary ingot is turned around and melted three times to obtain a finished ingot. It is required that the time interval from the consumable electrode to the primary melting is less than 8 hours, the time interval between the primary melting and the secondary melting of the ingot is less than 12 hours, and the time interval between the secondary melting and the tertiary melting is less than 15 hours, so as to ensure the uniformity of the ingot composition;
[0057] The smelting of the primary ingot and the secondary ingot are both carried out by vacuum consumable arc smelting. To ensure smooth exhaust of the electrode during the primary smelting process, the crucible ratio (electrode diameter / crucible diameter) is required to be less than 0.71. The primary ingot is firstly washed with a high-pressure air gun and clean water to remove dust on the surface and then dried. The gray and blackened positions on the surface of the primary ingot are then machined to completely remove the solidified shell at the position with a high content of impurity elements. The surface of the secondary ingot is brushed and polished to remove some volatile impurities in the smelting process.
[0058] The parameters of the above three smeltings are: in the first smelting, the vacuum degree of the smelting furnace is 0.5-0.8Pa, the leakage rate is less than 0.6Pa / min, the smelting current is 10-25kA, and the smelting voltage is 26-38V. After the first smelting is completed, the vacuum cooling time of the first ingot in the crucible is 7-9h, and the vacuum degree is less than 1Pa; in the second smelting, the leakage rate is controlled to be less than 0.5Pa / min, the vacuum degree is less than 0.5Pa, the smelting current is 13-27kA, and the smelting voltage is 26-38V. The smelting voltage is 28-42V. After the secondary smelting, the secondary ingot is vacuumed and cooled in the crucible for 8-10 hours, and the vacuum degree is less than 0.8Pa. During the tertiary smelting, the leakage rate is controlled below 0.3Pa / min, the vacuum degree is 0.01-0.1Pa, the smelting current is 4-25kA, and the smelting voltage is 20-43V. After the tertiary smelting, the finished ingot is vacuumed and cooled in the crucible for 9-12 hours, and the vacuum degree is less than 0.5Pa.
[0059] Step 3: Hot forming of bars:
[0060] First, the finished ingot is heated to 930-1080°C to complete 1-2 rounds of blanking forging, then 2-4 rounds of intermediate forging are completed at 770-910°C, and finally 2-5 rounds of forming forging are completed at 750-800°C to form bars with specifications of Φ150mm-Φ450mm;
[0061] Step 4: Heat treatment:
[0062] The obtained rod is kept at 750-800°C for 2h, and then subjected to AC ordinary annealing heat treatment to obtain a titanium alloy with medium-high strength, high toughness and damage tolerance.
[0063] In order to further verify the effect of the present invention, the inventors prepared a titanium alloy with medium-high strength, high toughness and damage tolerance by the following method:
[0064] Example 1
[0065] This embodiment provides a method for preparing a titanium alloy with medium-high strength, high toughness and damage tolerance. The target composition of the alloy is Al: 5%, Cr: 2.5%, V: 2.5%, O: 0.06%, and the balance is Ti and unavoidable impurity elements. The specific preparation steps are as follows:
[0066] Step 1: Electrode preparation:
[0067] Sponge titanium particles that meet GB / T 2524 are used, with a diameter range of 1 to 5 mm, and the impurity elements are detected as C≤0.006%, N≤0.003%, H≤0.001%, Si≤0.01%, Fe≤0.02%, Sn≤0.025%, and Cl≤0.03%; the impurity elements of vanadium aluminum alloy are detected as C≤0.02%, N≤0.01%, H≤0.01%, S≤0.01%, P≤0.01%, B≤0.01%, Si≤0.01%, Fe≤0.05%, and the particle size is less than 1 mm; the impurity elements of Cr single substance powder meet C≤0.005%, N≤0.01%, H≤0.003%, Si≤0.01%, Fe≤0.05%, and the powder particle size is less than 100 mesh; the impurities of single substance Al meet C≤0.02%, N≤0.01%, H≤0.01%, S≤0.01%, P≤0.01%, B≤0.01%, Si≤0.01%, Fe≤0.05%, and the particle size is less than 100 mesh; ≤0.008%, N≤0.001%, H≤0.003%, Si≤0.01%, Fe≤0.05%, particle size less than 3mm, the above raw materials meet the alloy use requirements; the weight of a single electrode block is 15kg, and then the weight of the intermediate alloy used in a single electrode block is calculated according to the target composition, and the mixing is completed by a mixer, and the mixing time is 120s. After the mixing is completed, the above raw materials are pressed into an electrode block with a size of 400mm (length) × 100mm (width) × 100mm (height); then they are welded into a consumable electrode through a plasma welding box. The electrode block assembly welding should be completed within 5h after the electrode block is pressed, and the electrode block should be loaded into the welding box for vacuuming. The welding should be completed in a plasma welding box under argon protection, and the argon pressure inside the welding box is required to be 1×10 6 Pa, monitor and detect the O and N elements inside the welding box before and during welding to ensure that the O content of the welding box is less than 450ppm and the N content is less than 600ppm;
[0068] Step 2: Ingot smelting:
[0069] A 1-ton vacuum consumable arc furnace (VAR) is used to firstly melt the consumable electrode to obtain a primary ingot. The crucible diameter is Ф200 mm. During the primary melting, the maximum vacuum degree of the melting furnace is 0.6 Pa, the leakage rate is less than 0.6 Pa / min, the melting current is 10.5 kA, and the melting voltage is 27 V. After the primary melting is completed, the primary ingot is vacuumed and cooled in the crucible for 7.5 hours. During the cooling process, the vacuum degree of the crucible is less than 1 Pa. Then, the primary ingot is rinsed with a high-pressure air gun and clean water, and dried and machined to remove impurities on the surface of the primary ingot.
[0070] The crucible diameter used for secondary smelting is 260 mm. The primary ingot obtained after machining is turned around and placed in the crucible for secondary smelting. During the secondary smelting, the leakage rate is less than 0.5 Pa / min, the vacuum degree is less than 0.5 Pa, the smelting current is 18 kA, and the smelting voltage is 32 V. After the secondary smelting is completed, the secondary ingot is vacuumed and cooled in the crucible for 8 hours, and the vacuum degree is less than 0.5 Pa. After being taken out of the furnace, the surface of the secondary ingot is brushed and polished to remove some volatile impurities in the smelting process.
[0071] The crucible diameter used for the third smelting is Ф340mm. The secondary ingot obtained after brushing and grinding is turned over for the third smelting. During the third smelting, the leakage rate is less than 0.3Pa / min, the vacuum degree of the furnace is less than 0.1Pa, the smelting current is 15kA, and the smelting voltage is 31V. After the third smelting, the finished ingot is vacuumed and cooled in the crucible for 9h, and the vacuum degree of the furnace is less than 0.3Pa. The head of the Ф340mm finished ingot prepared by the above method has normal macrostructure and no β spot defects, such as Figure 1 As shown;
[0072] Step 3: Hot forming of bars:
[0073] First, the finished ingot after three VAR smeltings is heated to 960℃ to complete 2-fire forging, then 2-fire intermediate forging is completed at 800℃, and then 3-fire forming forging is completed at 760℃ to form a Φ200mm bar; the head macrostructure of the obtained bar is inspected as follows: Figure 2 As shown, as well as T β -25℃ air burning tissue inspection Figure 3 As shown, the examinations were normal, and no β-plaque defects were found;
[0074] Step 4: Heat treatment:
[0075] The Φ200 mm rod is kept at 760°C for 2 hours and then subjected to AC ordinary annealing heat treatment to obtain a titanium alloy rod A with medium-high strength, high toughness and damage tolerance.
[0076] The metallographic photographs of the head of the titanium alloy bar A after ordinary annealing were checked to see if they met the requirements. Figure 4 As shown;
[0077] The performance of titanium alloy bar A was tested: tensile strength Rm = 1039MPa, yield strength Rp 0.2 =897MPa, elongation A = 23%, section shrinkage Z = 49%, fracture toughness K IC =131MPam 1 / 2 , fatigue crack growth rate da / dN(ΔK=11)=8.35×10 -6 mm / cycle.
[0078] Example 2
[0079] This embodiment provides a method for preparing a titanium alloy with medium-high strength, high toughness and damage tolerance. The target composition of the alloy is Al: 6.5%, Cr: 3%, V: 5%, O: 0.12%, and the remainder is Ti and unavoidable impurity elements. The specific preparation steps are as follows:
[0080] Step 1: Electrode preparation:
[0081] Use titanium sponge particles that meet GB / T 2524, with a diameter range of 2.5 to 5 mm, and impurity elements detected as C≤0.006%, N≤0.003%, H≤0.001%, Si≤0.01%, Fe≤0.01%, Sn≤0.020%, Cl≤0.02%; impurity elements of vanadium aluminum alloy are detected as C≤0.02%, N≤0.02%, H≤0.01%, S≤0.01%, P≤0.01%, B≤0.01%, Si≤0.01%, Fe≤0.025%, and particle size is less than 1 mm; impurity elements of Cr single substance powder meet C≤0.005%, N≤0.01%, H≤0.003%, Si≤0.01%, Fe≤0.06%, and powder particle size is less than 100 mesh; impurity elements of single substance Al meet The raw materials are C≤0.006%, N≤0.001%, H≤0.003%, Si≤0.01%, Fe≤0.08%, and the particle size is less than 3 mm. The above raw materials all meet the requirements for alloy use. The weight of a single electrode block is 25 kg. The weight of the intermediate alloy used in the single electrode block is calculated according to the target composition. The mixing is completed by a mixer. The mixing time is 180 seconds. After the mixing is completed, the above raw materials are pressed into an electrode block with a size of 350 mm (length) × 250 mm (width) × 200 mm (height). Then, the consumable electrode is welded by a plasma welding box. The electrode block assembly welding should be completed within 4 hours after the electrode block is pressed. The electrode assembly should be completed and the electrode block should be loaded into the welding box for vacuum. The welding should be completed in a plasma welding box under argon protection. The argon pressure inside the welding box is required to be 1×10 7 Pa, monitor and detect the O and N elements inside the welding box before and during welding to ensure that the O content of the welding box is less than 400ppm and the N content is less than 600ppm;
[0082] Step 2: Ingot smelting:
[0083] An 8-ton vacuum consumable arc furnace (VAR) is used to firstly melt the consumable electrode to obtain a primary ingot. The crucible diameter is Ф360mm. During the primary melting, the maximum vacuum degree of the melting furnace is 0.5Pa, the leakage rate is less than 0.5Pa / min, the melting current is 14kA, and the melting voltage is 34V. After the primary melting is completed, the primary ingot is vacuumed and cooled in the crucible for 8h. During the cooling process, the vacuum degree of the crucible is less than 0.5Pa. Then, the primary ingot is rinsed with a high-pressure air gun and clean water, and dried and machined to remove impurities on the surface of the primary ingot.
[0084] The crucible diameter used for secondary smelting is Ф440mm. The primary ingot after machining is turned around and placed in the crucible for secondary smelting. During the secondary smelting, the leakage rate is less than 0.4Pa / min, the vacuum degree is less than 0.6Pa, the smelting current is 18kA, and the smelting voltage is 36V. After the secondary smelting is completed, the secondary ingot is vacuumed and cooled in the crucible for 8.5h. The vacuum degree in the crucible is less than 0.5Pa. After being taken out of the furnace, the surface of the secondary ingot is brushed and then cleaned with a hair dryer.
[0085] The crucible diameter used for the third smelting is Ф520mm. The second ingot after brushing treatment is turned around for third smelting. During the third smelting, the leakage rate is less than 0.2Pa / min, the vacuum degree of the furnace is less than 0.1Pa, the smelting current is 10kA, and the smelting voltage is 26V. After the third smelting, the finished ingot is vacuumed and cooled in the crucible for 9h and the vacuum degree of the furnace is less than 0.3Pa.
[0086] The macrostructures of the head and tail of the Ф520mm finished ingot were checked and all were normal without β-spot defects.
[0087] Step 3: Hot forming of bars:
[0088] First, the finished ingot after three VAR smeltings was heated to 990℃ to complete 2-fire forging, then 4-fire intermediate forging was completed at 850℃, and then 5-fire forming forging was completed at 780℃, finally forming a Φ300mm bar; the macrostructure of the head and tail of the obtained bar was inspected and all were normal;
[0089] Step 4: Heat treatment:
[0090] The Φ300 mm rod is kept at 790°C for 2 hours and then subjected to AC ordinary annealing heat treatment to obtain a titanium alloy rod B with medium-high strength, high toughness and damage tolerance.
[0091] Then the properties of titanium alloy bar B were tested: tensile strength Rm = 1025MPa, yield strength Rp 0.2 =887MPa, elongation A = 22%, section shrinkage Z = 48%, fracture toughness K IC=128MPam 1 / 2 , fatigue crack growth rate da / dN(ΔK=11)=8.42×10 -6 mm / cycle.
[0092] Example 3
[0093] This embodiment provides a method for preparing a titanium alloy with medium-high strength, high toughness and damage tolerance. The target composition of the alloy is Al: 6%, Cr: 3.5%, V: 4%, O: 0.08%, and the remainder is Ti and unavoidable impurity elements. The specific preparation steps are as follows:
[0094] Step 1: Electrode preparation:
[0095] Use titanium sponge particles that meet GB / T 2524, with a diameter range of 2.5 to 5 mm, and impurity elements detected as C≤0.005%, N≤0.004%, H≤0.001%, Si≤0.01%, Fe≤0.02%, Sn≤0.025%, Cl≤0.03%; impurity elements of vanadium aluminum alloy are detected as C≤0.01%, N≤0.01%, H≤0.01%, S≤0.01%, P≤0.01%, B≤0.01%, Si≤0.01%, Fe≤0.04%, and particle size is less than 1 mm; impurity elements of Cr single substance powder meet C≤0.005%, N≤0.01%, H≤0.003%, Si≤0.01%, Fe≤0.05%, and powder particle size is less than 100 mesh; impurity elements of single substance Al meet The raw materials are C≤0.008%, N≤0.001%, H≤0.003%, Si≤0.01%, Fe≤0.05%, and the particle size is less than 3 mm. The above raw materials all meet the requirements for alloy use. The weight of a single electrode block is 40 kg. The weight of the intermediate alloy used in the single electrode block is calculated according to the target composition. The mixing is completed by a mixer. The mixing time is 180 seconds. After the mixing is completed, the above raw materials are pressed into an electrode block with a size of 400 mm (length) × 350 mm (width) × 250 mm (height). Then, the electrode blocks are welded into a consumable electrode by a plasma welding box. The electrode block assembly welding should be completed within 5 hours after the electrode block is pressed. The electrode block should be loaded into the welding box and vacuumed. The welding should be completed in a plasma welding box under argon protection. The argon pressure inside the welding box is required to be 1×10 7 Pa, monitor and test the O and N elements inside the welding box before and during welding to ensure that the O content in the welding box is less than 500ppm and the N content is less than 700ppm;
[0096] Step 2: Ingot smelting:
[0097] An 8-ton vacuum consumable arc furnace (VAR) is used to firstly melt the consumable electrode to obtain a primary ingot. The crucible diameter is Ф550mm. During the primary melting, the maximum vacuum degree of the melting furnace is 0.6Pa, the leakage rate is less than 0.4Pa / min, the melting current is 18kA, and the melting voltage is 37V. After the primary melting is completed, the primary ingot is vacuumed and cooled in the crucible for 8.5h. During the cooling process, the vacuum degree of the crucible is less than 0.5Pa. Then, the primary ingot is rinsed with a high-pressure air gun and clean water, and dried and machined to remove impurities on the surface of the primary ingot.
[0098] The crucible diameter used for secondary smelting is Ф660mm. The primary ingot after machining is turned around and placed in the crucible for secondary smelting. During the secondary smelting, the leakage rate is less than 0.3Pa / min, the vacuum degree is less than 0.4Pa, the smelting current is 22kA, and the smelting voltage is 39V. After the secondary smelting is completed, the secondary ingot is vacuumed and cooled in the crucible for 9h. The vacuum degree in the crucible is less than 0.3Pa. After being taken out of the furnace, the surface of the secondary ingot is brushed and then cleaned with a hair dryer.
[0099] The crucible diameter used for the third smelting is Ф720mm. The secondary ingot after brushing treatment is turned over for third smelting. During the third smelting, the leakage rate is less than 0.3Pa / min, the vacuum degree of the furnace is less than 0.1Pa, the smelting current is 12kA, and the smelting voltage is 29V. After the third smelting, the finished ingot is vacuumed and cooled in the crucible for 10h and the vacuum degree of the furnace is less than 0.1Pa.
[0100] The macrostructure of the head of the 720 mm finished ingot is as follows: Figure 5 As shown, and the tail low-magnification tissue is shown Figure 6 As shown, the inspection was normal, without β-spot defects; the 9-point components at the head and tail were extremely poor, as shown Figure 7-10 As shown: Al<2500ppm( Figure 7 )、V<1200ppm( Figure 8 )、Cr<2300ppm( Fig. 9 )、O<170ppm( Fig.10 ), showing that the finished ingot has uniform composition throughout the ingot;
[0101] Step 3: Hot forming of bars:
[0102] First, the finished ingot after three VAR smeltings is heated to 1000℃ to complete 2-fire forging, then 4-fire intermediate forging is completed at 895℃, and then 5-fire forming forging is completed at 800℃ to finally form a Φ400mm bar; the macrostructure of the bar head is as follows: Fig.11 As shown, and the tail low-magnification tissue is shown Fig.12 As shown, the examination was performed and all were normal;
[0103] Step 4: Heat treatment:
[0104] The Φ400 mm rod is kept at 780°C for 2 hours and then subjected to AC ordinary annealing heat treatment to obtain a titanium alloy rod C with medium-high strength, high toughness and damage tolerance.
[0105] The metallographic photographs of the head of the titanium alloy bar C after ordinary annealing were checked to see if they met the requirements. Fig.13 As shown; the mechanical properties of titanium alloy bar C are shown in Table 1, all of which meet the requirements.
[0106] Table 1 Performance results of Ø400mm bar after ordinary annealing
[0107]
[0108] The above examples illustrate that the titanium alloy prepared by the method for preparing the titanium alloy with medium-high strength, high toughness and damage tolerance can meet the application requirements in aviation structural parts.
[0109] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention.
[0110] It should be understood that the present invention is not limited to what has been described above and that various modifications and changes may be made without departing from its scope. The scope of the present invention is limited only by the appended claims.
Claims
1. A titanium alloy with medium-high strength, high toughness and damage tolerance, characterized in that: By weight percentage, it includes Al: 5.0% to 7.0%, Cr: 2.5% to 4%, V: 2.5% to 5.0%, O: 0.05% to 0.15%, C≤0.02%, N≤0.01%, H≤0.01%, Si≤0.01%, Fe≤0.08%, and the remainder is Ti and unavoidable impurity elements, wherein the total amount of impurity elements is less than 0.05%.
2. The titanium alloy with medium-high strength, high toughness and damage tolerance according to claim 1, characterized in that: The equivalent ranges of Al and Mo in the titanium alloy satisfy the following requirements: 15wt.%≤[Al]eq+[Mo]eq≤17.5wt.%, and 0.9≤[Al]eq / [Mo]eq≤1.
2.
3. A method for preparing a titanium alloy with medium-high strength, high toughness and damage tolerance according to claim 1 or 2, characterized in that: The specific steps are as follows: Step 1: Electrode preparation: The weight of titanium sponge, master alloy and other elemental metals is calculated according to the weight percentage, and then the materials are weighed, mixed, the electrode blocks are pressed and the electrodes are welded to form consumable electrodes; Step 2: Ingot smelting: Firstly, a consumable electrode is melted once in a vacuum consumable arc furnace to obtain a primary ingot, then the primary ingot is turned around and melted twice to obtain a secondary ingot, and finally the secondary ingot is turned around and melted three times to obtain a finished ingot; Step 3: Hot forming of bars: The obtained finished ingot is subjected to blanking forging, intermediate forging and forming forging in sequence to finally obtain the required bar; Step 4: Heat treatment: The obtained rod is subjected to ordinary annealing heat treatment to obtain a titanium alloy with medium-high strength, high toughness and damage tolerance.
4. The method for preparing the titanium alloy with medium-high strength, high toughness and damage tolerance according to claim 3, characterized in that: In step 1, the titanium sponge satisfies C≤0.008%, N≤0.005%, H≤0.003%, Si≤0.01%, Fe≤0.04%, Sn≤0.03%, and Cl≤0.03%; the intermediate alloy is a vanadium aluminum alloy, and its impurity elements satisfy C≤0.05%, N≤0.03%, H≤0.01%, S≤0.01%, P≤0.01%, B≤0.01%, Si≤0.02%, and Fe≤0.10%; the impurity elements of the single substance Cr powder satisfy C≤0.005%, N≤0.01%, H≤0.005%, Si≤0.01%, and Fe≤0.10%; the remaining Al element is added in the form of single substance Al, and the impurity elements satisfy C≤0.01%, N≤0.001%, H≤0.003%, Si≤0.01%, and Fe≤0.08%.
5. The method for preparing the titanium alloy with medium-high strength, high toughness and damage tolerance according to claim 4, characterized in that: In step 1, the particle size of the titanium sponge is less than 5 mm, the particle size of the vanadium aluminum alloy is less than 1 mm, the particle size of the single Al is less than 3 mm, and the particle size of the single Cr powder is less than 100 mesh.
6. The method for preparing the titanium alloy with medium-high strength, high toughness and damage tolerance according to claim 3, characterized in that: In step 2, the dust on the surface of the obtained primary ingot is washed off with a high-pressure air gun and clean water and then dried, and then the gray and blackened parts of the surface of the primary ingot are machined; the surface of the obtained secondary ingot is brushed and polished.
7. The method for preparing the titanium alloy with medium-high strength, high toughness and damage tolerance according to claim 3, characterized in that: In step 2, during the primary smelting, the vacuum degree of the smelting furnace is 0.5-0.8 Pa, the leakage rate is less than 0.6 Pa / min, the smelting current is 10-25 kA, and the smelting voltage is 26-38 V. After the primary smelting is completed, the primary ingot is vacuumed and cooled in the crucible for 7-9 hours, and the vacuum degree is less than 1 Pa. During the secondary smelting, the leakage rate is controlled to be less than 0.5 Pa / min, the vacuum degree is less than 0.5 Pa, the smelting current is 13-27 kA, and the smelting voltage is 26-38 V. The voltage is 28-42V. After the secondary smelting, the secondary ingot is vacuumed and cooled in the crucible for 8-10 hours, and the vacuum degree is less than 0.8Pa. During the tertiary smelting, the leakage rate is controlled below 0.3Pa / min, the vacuum degree is 0.01-0.1Pa, the smelting current is 4-25kA, and the smelting voltage is 20-43V. After the tertiary smelting, the finished ingot is vacuumed and cooled in the crucible for 9-12 hours, and the vacuum degree is less than 0.5Pa.
8. The method for preparing the titanium alloy with medium-high strength, high toughness and damage tolerance according to claim 3, characterized in that: In step 3, the finished ingot is first heated to 930-1080°C to complete 1-2 rounds of blank forging, then 2-4 rounds of intermediate forging are completed at 770-910°C, and finally 2-5 rounds of forming forging are completed at 750-800°C.
9. The method for preparing the titanium alloy with medium-high strength, high toughness and damage tolerance according to any one of claims 3 to 8, characterized in that: The tensile strength of the titanium alloy is Rm≥1000MPa, and the yield strength is Rp 0.2 ≥880MPa, elongation A≥18%, section shrinkage Z≥45%, fracture toughness K IC ≥120MPam 1 / 2 , fatigue crack growth rate da / dN≤8.92×10 -6 mm / cycle.
10. Use of the titanium alloy with medium-high strength, high toughness and damage tolerance according to claim 1 or 2, or the titanium alloy prepared by the method for preparing the titanium alloy with medium-high strength, high toughness and damage tolerance according to any one of claims 3 to 8 in aviation structural parts.
Citation Information
Patent Citations
Damage tolerant medium-strength titanium alloy
CN105506379A
Low-cost and high-strength high-titanium alloy and preparation method thereof
CN107746992A
High strength titanium alloy and its production
JP1997194969A
Chromium-added titanium alloy having stress corrosion resistance and manufacturing method therefor
WO2024075894A1